Strength Analysis for Cage of Planetary Wheel Needle Roller Bearing - Yubo Wang; Haisheng Yang; Manjun Xu; Yongcun Cui; Sier Deng (Jixie chuandong, 2021)
Aiming to solving the problem of cage failure under revolution-rotation，based on the dynamics theory of rolling bearing，the dynamics differential equations of needle roller bearing coupled with revolution-rotation working condition are established，and GSTIFF variable step length integral algorithm is adopted to solve the bearing. Cage stress is used to evaluate cage strength，and the influence of bearing working conditions on cage stress is studied to guide cage material selection. The results show that the cage stress with revolution is obviously greater than that without revolution. The impact force between the needle roller and the cage mainly affects the stress at the contact place where is between the needle roller and the cage，which increases with the increase of the impact force，while the centrifugal force of the cage mainly affects the stress at the angle of the beam slope of the cage，which increases with the increase of the centrifugal force. The 0Cr18Ni9Ti can be selected when revolution velocity is low，20CrMo can be selected when revolution velocity is high.